Short-term Fasting Induces Alternate Activation of Orexin and Melanin-concentrating Hormone Neurons in Rats. (21st May 2022) - Linehan, Victoria; Hirasawa, Michiru
Highlights: Orexin and MCH neurons have complementary roles in response to fasting. MCH neurons are activated during early fasting, which would prevent weight loss. Orexin neurons show a delayed activation, which would promote food-seeking behavior. These alternating changes may optimize energy balance during fasting. Abstract: Orexin and melanin-concentrating hormone (MCH) neurons constitute the energy balance circuitry that coordinates the fasting response. Orexin neurons mediate food foraging at the expense of energy storage, while MCH neurons promote energy storage by reducing energy expenditure and increasing food intake. It is unknown if these cell groups undergo plastic changes as hunger and metabolic changes escalate over time during fasting. To address this, we performed in vitro electrophysiological recording on orexin and MCH neurons in the lateral hypothalamus and perifornical area from rats fasted for 12 or 24 h or fed ad-libitum . Orexin neurons showed a transient decrease in presynaptic glutamate release at 12 h. This turned to an increase at 24 h of fasting, while membrane potential depolarized and AMPA receptor conductance increased. In contrast, MCH neurons were transiently depolarized at 12 h fasting along with increased presynaptic glutamate release. These changes reversed at 24 h, while the number of AMPA receptors decreased. Our results indicate that MCH neurons are preferentially activated during the early phase of fasting (12 h), which would protect against weight loss. With a longer fast, orexin neurons become activated, which would promote arousal and exploratory activity required for foraging behaviors. This alternating activation of these cell groups may reflect a dynamic balance of energy conservation and foraging behaviors to optimize energy balance during ongoing fasting.